2016
DOI: 10.1111/pde.12772
|View full text |Cite
|
Sign up to set email alerts
|

Penile and Scrotal Swelling: An Underrecognized Presentation of Crohn's Disease

Abstract: Penile and scrotal swelling can occur as an extraintestinal manifestation of CD and is thought to be an uncommon form of MCD. In boys, genital swelling typically precedes intestinal CD. Treatment of the underlying CD with systemic medications was most helpful in this series. An evaluation for CD is necessary in all patients presenting with unexplained genital swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Metastatic Crohn's disease in children is rare—a literature review in 2009 found 28 individual case reports spanning 40 years, with genital Crohn's disease accounting for 21 of the 28 cases . Cutaneous genital metastatic Crohn's disease in children may also present with persistent nontender nodules or induration or penile and scrotal swelling in boys . In the majority of these cases, presentation predated the diagnosis of Crohn's disease, which is in contrast to the adult population .…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic Crohn's disease in children is rare—a literature review in 2009 found 28 individual case reports spanning 40 years, with genital Crohn's disease accounting for 21 of the 28 cases . Cutaneous genital metastatic Crohn's disease in children may also present with persistent nontender nodules or induration or penile and scrotal swelling in boys . In the majority of these cases, presentation predated the diagnosis of Crohn's disease, which is in contrast to the adult population .…”
Section: Discussionmentioning
confidence: 99%
“…HAE most commonly affects the skin on the extremities, with the onset of symptoms usually in childhood. Other rare causes of isolated acute genital swelling reported in childhood included idiopathic lymphoedema, metastatic Crohn's disease , juvenile dermatomyositis , and fixed drug eruptions . Noncutaneous involvement of HAE, such as the gastrointestinal tract, brain, kidney, and pancreas, often causes a delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 A recently published case series of five patients with metastatic Crohn's disease showed that systemic anti-TNFα biologic agents (adalimumab or infliximab) were the most effective, but responses were varied and frequent relapse was common. 4 Two out of the five patients in the study eventually required a combination of anti-TNFα and methotrexate, which demonstrated lasting benefit. 4 Circumcision had a high complete resolution rate of 80% and patients on continuous long-term therapy were shown to have complete resolution at followup (nine years).…”
Section: Discussionmentioning
confidence: 99%
“…4 Two out of the five patients in the study eventually required a combination of anti-TNFα and methotrexate, which demonstrated lasting benefit. 4 Circumcision had a high complete resolution rate of 80% and patients on continuous long-term therapy were shown to have complete resolution at followup (nine years). 3 Metastatic Crohn's disease of the genitalia is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation